An analytical study of the poems of the poet Widad Rahim Al-Wasiti (Journal of the College of Basic Education, 2025)
The poet Wedad’s poems are distinguished by their depth, transparency, and sincere expression of human feelings that touch the hearts of readers. This is what prompted us to examine it and study it as an analytical artistic study that aims to form a deep understanding of her poetic message and its hidden meanings and to explore its impact on readers and society in general. The importance of the analytical study of Widad Al-Wasiti’s poetry lies in shedding light on important artistic and human aspects of her distinguished poetry. Through analyzing the symbols, images, and poetic methods that she uses, researchers and those interested in Arabic literature can understand the world of Wadi Al-Wasiti in a deeper and broader way, and appreciate her artistic and cultural influence on Arabic literature. The research aims to provide expanded and comprehensive explanations about Widad Al-Wasiti’s poetry, and to understand the extent of its influence and importance in the Arab literary arena. The study also aims to highlight the aesthetic, creative and philosophical aspects of her poetry, and monitor the beauty of her poetic language. The research relies on the foundations of the faithful and analytical approach, which seeks to identify the linguistic and pictorial aspects and methods in reading Widad Al-Wasiti’s poetry and drawing an artistic picture of it.